2021
DOI: 10.2478/hjbpa-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Quality Management for Leather Industry to Increase Competitiveness in the Global Market

Abstract: The Indonesian government is targeting leather products, especially from West Java to become one of the export commodities that will encourage national economic growth. The existence of a leather industry particularly in the city of Garut has attracted many Indonesian researchers over the years to investigate the condition through many fields of research. However, the latest research identified several barriers related to the leather business development in Garut city, which was related to the optimization rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
1
0
6
Order By: Relevance
“…Keberadaan UMKM jelas berdampak signifikan terutama dalam perkembangan kewirausahaan di Indonesia yang telah mendapatkan perhatian serius dari pemerintah sehingga melahirkan programprogram dan kebijakan pemberdayaan usaha kecil agar dapat tumbuh dan diandalkan sebagai salah satu ketahanan nasional dari sektor ekonomi. Meskipun demikian, UMKM Indonesia masih menghadapi berbagai tantangan yang belum mampu terselesaikan sehingga membuat keberadaan sebagian besar dari UMKM tersebut tidak berumur panjang dalam persaingan usaha (Azis et al, 2019;Hapsari, 2014;Irjayanti & Azis, 2021).…”
Section: Gambar 1 Permasalah Yang Dihadapi Pelaku Usahaunclassified
See 2 more Smart Citations
“…Keberadaan UMKM jelas berdampak signifikan terutama dalam perkembangan kewirausahaan di Indonesia yang telah mendapatkan perhatian serius dari pemerintah sehingga melahirkan programprogram dan kebijakan pemberdayaan usaha kecil agar dapat tumbuh dan diandalkan sebagai salah satu ketahanan nasional dari sektor ekonomi. Meskipun demikian, UMKM Indonesia masih menghadapi berbagai tantangan yang belum mampu terselesaikan sehingga membuat keberadaan sebagian besar dari UMKM tersebut tidak berumur panjang dalam persaingan usaha (Azis et al, 2019;Hapsari, 2014;Irjayanti & Azis, 2021).…”
Section: Gambar 1 Permasalah Yang Dihadapi Pelaku Usahaunclassified
“…Permasalahan yang teridentifikasi dari para pelaku usaha juga disebutkan oleh berbagai temuan literature bersama dengan persoalan lainnya diantaranya: 1. Manajemen usaha (Hapsari, 2014;Irjayanti & Azis, 2021;Morgan & Sisak, 2016;Tambunan, 2019). Usaha mikro dan kecil ditemukan banyak menggunakan pendekatan tradisional untuk mengelola usahanya.…”
Section: Gambar 1 Permasalah Yang Dihadapi Pelaku Usahaunclassified
See 1 more Smart Citation
“…In Pakistan, it is reported by Mehmood and Ali (2020) that the performance of the leather footwear industry in the country has been influenced significantly by the growth strategies adopted, such as advertising and promotion. In Indonesia, it is stated by Irjayanti and Azis (2021) that quality management through technological advancement and diversification increases the competitiveness of the leather industry in the global market. A study conducted by Gupta and Dhamija (2019) indicated that capacity advancement, pricing, technological advancement and diversification are critical components of the growth strategies that influence the performance of the Indian leather industry.…”
Section: Literature Review 21 Empirical Reviewmentioning
confidence: 99%
“…Аналіз останніх досліджень і публікацій. Вивченню факторів формування якості та безпечності шкіряних матеріалів присвячено праці вітчизняних вчених: Н. Попович [2], О. Андреєвої, С. Гаркавенко, В. Паламар [4] та ін., а також закордонних: M. Irjayanti, A. Mulyono Azis [5], B. Amde [6] тощо. У працях зазначених науковців розглянуто вплив низки факторів на якість та безпечність різних шкіряних матеріалів.…”
Section: у п р а в л і н н я я к і с т ю т а б е з п е ч н і с т ю по...unclassified